Discovery of novel potent GPR40 agonists containing imidazo[1, 2-a]pyridine core as antidiabetic agents. Issue 13 (1st July 2020) - Ye, Zhiwen; Liu, Chunxia; Zou, Feng; Cai, Yan; Chen, Bin; Zou, Yuxing; Mo, Jiaxian; Han, Ting; Huang, Wenlong; Qiu, Qianqian; Qian, Hai
Graphical abstract: Abstract: Free fatty acid receptor 1 (FFA1 or GPR40) has been studied for many years as a target for the treatment of type 2 diabetes mellitus. In order to increase potency and reduce hepatotoxicity, a series of novel compounds containing imidazo[1, 2- a ]pyridine scaffold as GPR40 agonist were synthesized. Compound I-14 was identified as an effective agonist as shown by the conspicuous drop in blood glucose in normal and diabetic mice. It had no risk of hepatotoxicity compared with TAK-875. Moreover, good pharmacokinetic (PK) properties of I-14 were observed (CL = 27.26 ml/h/kg, t1/2 = 5.93 h). The results indicate that I-14 could serve as a possible candidate to treat diabetes.